Causative Agent(s) : Quranic Perspective - Mohammed Muneer'deen, Olodo Al-Shafi'i; Lazim, Omar; Mohd Safri, Ali (2016)
There are many writings on the axiomic (i.e Qaḍiyyah musallamah) scientific causative agent(s), both from the East and the West. Muslims, as well as non-Muslims have also said a lot from their own perspec-tives. But none have been able to categorically specify whether or not the notion is totally rejected from the Qur’anic point of view, or it is totally approved. This paper thus discusses the notion, which sees the Qur’an as a model for anything and everything. The paper posits that Philosophy, Sciences, Technology, and Religion un-animously agree that all thing have got a cause, and hence all ‘causeds’ have a source. Philosophy is yet to substantively satisfy our quest, science is still struggling to allay our fears, technology is yet to convince our minds of its danger(s), and religion has not been fully allowed to freely proof its worth, where then lays the ‘causer’, the ‘medium’ and the ‘caused’? The paper accesses some philosophic notions of the causative agent(s) in the light of the Qur’anic interpretation of such. The major focus of the paper is on some Qur’anic verses and instances relevant to ‘cause’ and ‘effect’. The paper submits that ‘the notion of the causative agent(s) without exploring its religio-Divine sources is